CHARACTERISTICS OF SLEEP DISORDERS IN ADOLESCENTS WITH CHRONIC GASTRITIS AT THE NATIONAL PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of sleep disorders in adolescents with chronic gastritis and identify some related factors. Subjects and methods: A cross-sectional descriptive study was conducted on 150 adolescents diagnosed with chronic gastritis at the National Pediatric Hospital. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQ). Results: The prevalence of sleep disorders was 34.7%, with mild sleep disorders being the most common (20.0%), followed by moderate (9.3%) and severe (5.4%). The average PSQI score was 7.7 ± 3.1. Common sleep disorders included shallow sleep, easy awakening (70.0%), difficulty falling asleep (60.0%), multiple awakenings during the night (55.3%), and nighttime sleep duration of less than 6 hours (50.0%). Sleep disorders were associated with age group, puberty status, screen time exceeding 3 hours per day, and academic pressure (p < 0.05). Conclusion: Sleep disorders are common in adolescents with chronic gastritis and are related to both biological and lifestyle-psychological factors. Screening and intervention are crucial. Sleep disorder interventions are essential for the holistic treatment of adolescents with chronic gastritis and for improving their quality of life.
Keywords: chronic gastritis; sleep disorder; adolescents; PSQI.